Aspek Hukum Perusahaan Penyelenggaraan Angkutan Umum Berbasis Teknologi Informasi (TAWAZUN: Journal of Sharia Economic Law, 2021)
This paper aims to find out how the legal aspects of companies operating special rental transportation are regulated based on the Regulation of the Minister of Transportation (Permenhub.) of the Republic of Indonesia Number 118 of 2018 which is amended by Permenhub. Number 17 of 2019. Transportation is the movement of people or goods from one place to another by using a vehicle in the road traffic room. The information technology system-based transportation adapum is a mode of transportation in the form of legal entities and micro-enterprises or small-scale business actors connecting from one place of origin to one's destination, where the ordering method uses an information technology system and the amount of the fare is listed in the application. Companies in the form of legal entities in the form of Limited Liability Companies, BUMN, BUMD, and Cooperatives as well as micro business actors or small business actors established in accordance with the provisions of laws and regulations. The form of this special rental transportation company is not in accordance with Law Number 22 of 2009 and Article 79 of Government Regulation Number 74 of 2014 concerning the Implementation of Public Transportation.